The theological programme of Mark exegesis and function of Mark 1:1,2-15 - Filannino, Francesco 1988- (Tübingen Mohr Siebeck, 2021)
"The first chapters of literary works are indispensable to understanding them. This is also true of the Gospels. Francesco Filannino shows that the introductory section of Mark's Gospel (Mark 1:1-15) is an important key to accessing the whole narrative, because it anticipates the main contents of the evangelist's theology."
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Theology; Bible; Theology; Criticism, interpretation, etc